Reversible switching of structural and plasmonic properties of liquid-crystalline gold nanoparticle assemblies. Issue 5 (13th January 2016) - Lewandowski, W.; Łojewska, T.; Szustakiewicz, P.; Mieczkowski, J.; Pociecha, D.
Abstract : An active plasmonic material based on Au nanoparticles is shown to reversibly switch with temperature between two long-range ordered structures. Abstract : Hybrid materials built of spherical gold nanoparticles with three different sizes covered with (pro)mesogenic molecules have been prepared. Small-angle X-ray diffraction studies showed that after thermal annealing most of the obtained materials formed long-range ordered assemblies. Variation of the (pro)mesogenic ligand architecture enabled us to achieve a switchable material, which could be reversibly reconfigured between 3D long-range ordered structures with tetragonal and face centred cubic symmetries. This structural reconfiguration induces changes to the plasmonic response of the material. This work demonstrates that it is possible to use LC-based self-assembling phenomena to prepare dynamic materials with structural properties important for the development of active plasmonic metamaterials.